(3OhQ GdEYdGe GdJQHhj aj ecGaMI GdeNOQGJ (B:s (3cja jYGdL GdGYdGe GdYQHj eTcdI GdeNOQGJ OQGSI ejOGfjI (B/s - (3NVhQ, COjHs ((3GdLRGFQ (B:s (3OGQ GdCjGe ,s, 1999)
(3eGgj WHjYI GdYdGbI GdbGFeI Hjf GdEYdGe h GdJQHjI h eG eSGMI GdgGeT GdeTJQc Hjf gGJjf GdaYGdjJjf? eGgj GHQR fXQjGJ GdJCKjQ h GSJQGJjLjGJ GdEbfGY h GJLGgGJ GdJCKjQ ? h Ydi VhA GdefWdbGJ GdfXQjI(B: (3cja jYGdL GdGYdGe GdYQHj eTcdI GdeNOQGJ? GdUMGaI GdYQHjI GdebQhAI cja JJUOi deYGdLI eTcdI GdeNOQGJ ? eGgj GdNUGFU GdJj JbOegG gPg GdUMGaI dgPg GdeTcdI (B((3JMdjd eVehf (B1187 (3eGOI UMajI(B) (3GdGPGYI YeheG h GdOQGeG GdEPGYjI NUhUG cja JYGdL eTcdI GdeNOQGJ? h eGgj GdSeGJ GdeejRI dgPg GdeYGdLI (B...(3Ef GdeYGdLI GdEYdGejI GdYQHjI deTcdI GdeNOQGJ dG JJe aj aQGZ Hd gj eYGdLI eMcheI HTQWgG GdJGQjNj GdGLJeGYj h JYcS SjGbG SjGSjG KbGajG eYjfG jSYi gPG GdHMK GdejOGfj dGSJNdGU GLGHGJ Yf gPg GdGSFdI h ddeSGgeI aj OQGSI GdeeGQSI GdGYdGe h GdhUhd Gdi fJGFL jecf GSJNOGegG dGZfGA gPg GdeeGQSI h QHeG dGYGOI GdfXQ aj WHjYJgG(B..s
Keywords: (3GdEYdGes; (3GdJQHjIs; (3GdeNOQGJ s